Model Pembelajaran Kontekstual (Kelompok Kerja) untuk Meningkatkan Pemahaman Materi Melukis Segitiga, Garis Tinggi, Garis Berat, dan Garis Sumbu pada Mata Pelajaran Matematika Kelas VII-E MTs Negeri Tembelang - Sunani (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
The contextual method (Work Group) is a learning concept that helps teachers relate material to real-world situations of students and encourages students to make connections between the knowledge they have and its application in their lives as members of society which is structured in a group-oriented learning model. This research was procedurally using a systematic or sequence of class action research design (CAR). This research model is very much in line with the role and function of the teacher who always takes corrective action in every post-teaching activity (KBM). The problems that arise and develop in this study are formulated as follows: (1) how to improve understanding of the material for painting triangles, height lines, bisectors, weight lines, and axes in Mathematics in Class VII-E MTs Negeri Tembelang 2010 Academic Year /2011 using the contextual method (Working Group)? and (2) whether efforts to increase understanding of the material for painting triangles, heights, division lines, weight lines and axes in Mathematics Subjects in Class VII-E MTs Negeri Tembelang Academic Year 2010/2011 using the contextual method (Working Group) show results satisfactory?. The conclusion is that by using this contextual teaching and learning model (Contextual Teaching and Learning, CTL), the teacher can seek to improve understanding of the material for painting triangles, heights, division lines, weight lines, and axis lines in Mathematics Subjects in Class VII-E MTs Negeri Tembelang 2010/2011 Academic Year.